EPISTEMOLOGI ISLAM DAN REFORMASI WAWASAN PENDIDIKAN - Buseri, Kamrani (Jurnal Ilmiah Peuradeun, 2015)
Islamic education including socio-humanistic category that can be developed from its epistemology. Education reforms are absolutely necessary because there has been a weakness of good educational philosophy, theory and operations, with the main focus is the reform of insight. This paper examines the epistemological aspects of Islam as a basic step on education reform governance scheme Islamic thought as Theo anthropocentric, appreciate sensory empirical truth, logic, ethics, and transcendental. Application of this epistemology appropriately be able to overcome the problems of education weaknesses. Results of research paper put forward some Islamic education reform paradigm involves understanding the Islamic system; True intentions as a basic motivation; aware of the position of truth, goodness and beauty; embedded core value of the Divine as well as the characteristics of Islamic education; live up to the family as the initial source of truth; develop the total and holistic personality; and the implementation of the Divine in education management.